Disease and Treatment-Related Burden in Patients With Acromegaly Who Are Biochemically Controlled on Injectable Somatostatin Receptor Ligands - Fleseriu, Maria; Molitch, Mark; Dreval, Alexander; Biermasz, Nienke R.; Gordon, Murray B.; Crosby, Ross D.; Ludlam, William H.; Haviv, Asi; Gilgun-Sherki, Yossi; Mathias, Susan D. (Frontiers in Endocrinology, 2021)
Medical treatment for acromegaly commonly involves receiving intramuscular or deep subcutaneous injections of somatostatin receptor ligands (SRLs) in most patients. In addition to side effects of treatment, acromegaly patients often still experience disease symptoms, even when therapy is successful in controlling GH and IGF-1 levels. Symptoms and side effects can negatively impact patients’ health-related quality of life. In this study, we examine the disease- and treatment-related burden associated with SRL injections as reported through the use of the Acromegaly Treatment Satisfaction Questionnaire (Acro-TSQ © 2016 Chiasma Inc, USA), and clinician-reported symptom severity through the Acromegaly Index of Severity (AIS). Patients included in this analysis were enrolled in a randomized phase 3 study, were biochemically-controlled (an IGF-1 < 1.3 x the upper limit of normal [ULN] or an average GH < 2.5ng/ml) and receiving SRL injections for ≥6 months with a stable dose of either long-acting octreotide or lanreotide monotherapy for ≥4 months. The sample (N=91) was 65% female, 91% Caucasian, with a mean (standard deviation [SD]) age of 53 (11) years. Two-thirds of patients reported that they still experience acromegaly symptoms; 82% of these said they experience symptoms all of the time. Three-fourths experienced gastrointestinal (GI) side effects after injections, and 77% experienced treatment-related injection site reactions (ISRs). Patients commonly reported that these interfered with their daily life, leisure, and work activities. Those with higher symptom severity, as measured by the AIS, scored significantly worse on several Acro-TSQ domains: Symptom Interference, GI Interference, Treatment Satisfaction, and Emotional Reaction. Despite being biochemically controlled with injectable SRLs, most patients reported experiencing acromegaly symptoms that interfere with daily life, leisure, and work. GI side effects and ISRs were also common. This study highlights the significant disease burden associated with injectable SRLs and the need for therapeutic alternatives for optimal symptomatic control of acromegaly.